Pengaruh Penggunaan Metode Minimal Pairs terhadap Kemampuan Fonologi pada Anak Down Syndrome di Surakarta - Asyifa Aisyah Nuraini; Dodiet Aditya Setyawan; Hafidz Triantoro Aji Pratomo (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Down syndrome is a common genetic condition associated with intellectual limitations, specific health conditions, developmental delays, and distinctive physical characteristics. Children with Down syndrome experience delays in language development, particularly in phonological, syntactic, and pragmatic aspects, resulting in slower acquisition of speech sounds compared to typically developing children. Minimal pairs is a linguistically based, production-oriented approach that uses pairs of words differing by only one phoneme to train sound discrimination. Objectives: This study aims to determine the effect of the use of the Minimal pairs method on the phonological abilities of children with Down syndrome in Surakarta. Methods: This study employed a quantitative approach with an experimental design using a one-group pre-test–post-test design. The sampling technique used was purposive sampling, with a total of 6 participants. Data analysis was conducted using parametric statistical tests, namely the Shapiro-Wilk test and the Paired T-Test. Results: The results of the Paired T-Test showed a p-value (Sig.) of 0.037, where p < 0.05, indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. This means that there is a significant difference in phonological abilities of children with Down syndrome before and after the intervention. Conclusion: There is a significant effect of the use of the Minimal pairs method on the phonological abilities of children with Down syndrome in Surakarta. Keywords: Children, Down syndrome, Phonology, Minimal Pairs.